Leave Management Reporting System (LMS Reporting) / Cheng Keang Lim - Cheng, Keang Lim (2004)
Leave Management System (LMS) Reporting is an analysis tools that used to generate report. This system is implemented in many large companies to manage their staff attendance and leave. It can generate report base on the ISO standard. Besides, it also helps to analyze staff leave in a more organize method. This purpose of my thesis is to develop aLMS Reporting that integrate into the FSKTM LMS. As the major function of this system is to generate reports, Crystal Report 9.0 has been chosen to help in generating the dynamic reports. The system is running on the .NET framework and ASP.NET is use to develop the system. For LMS Reporting database, SQL Server 2000 is used store the data and ADO.NET is used to access data. Basically, LMS Reporting is an application service that allows administrator and staffs in FSKTM to generate the report either in bar chart or table form, based on the users' criteria. This system provides filtering function that allows users to access record in different method such as select by department, name, academic staff, non-academic staff and date. Besides that, this system allows staff to convert their leave balance to cash amount or bring forward leave balance to next year. As a conclusion, LMS reporting is a tool that helps users to perform the analysis easily. It also generates a report based on the format, criteria and requirements stated by the end users. With these advance features, LMS Report save users time, cost and provide high performance.